Exploring the Drivers of Customer Loyalty in the Restaurant Industry: A Systematic Literature Review and Future Research Agenda - Purnami, Ni Made; Nurcaya, I Nyoman (Jurnal Ilmiah Manajemen & Bisnis, 2025)
The purpose of this paper is to provide a comprehensive analysis of the determinants of customer loyalty in the restaurant industry and identify opportunities for future research. A systematic literature review was conducted using the PRISMA protocol, involving a final sample of 33 articles published between 2015 and 2024. The databases used include Scopus journals, with inclusion and exclusion criteria applied to ensure relevance and quality. Key factors influencing restaurant loyalty were identified, including satisfaction, service quality, and food quality, which are crucial for fostering long-term relationships and ensuring repeated patronage. Additional significant factors include brand image, price fairness, sensory experiences, sustainable practices, and customer engagement. Enhancing customer satisfaction through excellent service, quality food, and positive dining experiences is paramount for building a loyal customer base. The study highlights key factors for improving customer loyalty in restaurants, such as satisfaction, service quality, and sustainable practices. It offers valuable insights for both academics and practitioners, suggesting future research on mobile food-ordering apps and sustainability. The findings emphasize the importance of understanding these factors to develop effective strategies for enhancing customer satisfaction and loyalty.